Program Narasi KATA (Boneka Tangan) sebagai Media Edukasi Pengolahan Stres pada Anak Korban Bullying Guna Menghindari Terjadinya Post-Traumatic Stress Disorder - Hardiyanto, Sigit; Khairina, Nadhilah; Hatta, Tengku Zaifach; Soraya, Rani; Putri, Mayolla Fransiska; Novrizal, Baihaqi Septiansyah; Lubis, Faizal Hamzah; Zuhdi, Abdurrahman (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The KATA (Hand Puppet) Narrative Program as an Educational Media for Stress Processing in Children Victims of Bullying to Avoid the Occurrence of Post-Traumatic Stress Disorder is to provide an understanding of traumatic events while controlling the emotional movements of children who are victims of bullying and acting as a medium to foster a sense of trust children at the Baitul Ummah Wal Amal Orphanage. Method: The method used in this activity is carried out in several stages, namely providing education, encouraging invitations, building imagination from a story through hand puppets can relax the psychology of partners, especially children who are victims of bullying. Results: The results obtained in this activity can be seen in the control of the emotional movements of children who are victims of bullying. Conclusion: This activity also has a role as a medium to foster children's self-confidence at the Baitul Ummah Wal Amal Orphanage.